De la igualdad natural a la igualdad de oportunidades. Revisitando la teoría igualitarista frente al bienestar y la desigualdad en América Latina - Hernández Bazán, Freddy (2020)
The present article intends a revision of the theoretical and philosophical foundations regarding inequality as a contribution to the justification of redistributive measures and well-being asymmetries tackling in high and persistent inequality scenarios. It presents, first, an analytical approach about the main conceptualizations of inequality within what has been termed as the egalitarian contemporary theory, and second, an empirical analysis which associates annual inequality and well-being in 18 Latin American countries from 2001 to 2013 controlling by welfare regime typologies. One of its main results points out to a negative and statistically significant correlation between inequality and well-being within countries with a more egalitarian and decommodifying welfare regimes.